PENGARUH MORAL DAN RELIGI TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PENGETAHUAN PERPAJAKAN SEBAGAI VARIABEL MODERASI - Mutiara, Shalsabilla Desi; Trisnawati, Estralita (Jurnal Kontemporer Akuntansi, 2025)
Taxes are mandatory and compulsory contributions to the state, so taxpayer compliance or non-compliance is a decision made by an individual based on behavioral or moral considerations. Tax revenue will increase along with increased taxpayer compliance in reporting their assets. In reality, the level of taxpayer compliance in submitting Annual Tax Returns has not reached the target set by the Directorate General of Taxes (DGT), so taxes cannot function as an instrument for income redistribution and reducing social inequality. The purpose of this study is to analyze the influence of morality and religion on taxpayer compliance, with tax knowledge as a moderating variable. Individual taxpayers registered at the Jakarta City Tax Office (KPP Pratama) were used as the study population, and the sampling method was purposive sampling. The analytical measuring tool used to test the hypothesis in this study is moderated regression analysis (MRA) using IBM SPSS (Statistical Program for Social Science) software version 23. The results of the study show that the morality variable is significantly able to increase the compliance of individual taxpayers, the religion variable is significantly able to increase the compliance of individual taxpayers, the tax knowledge variable is also able to strengthen the influence of morality and religion in increasing the compliance of individual taxpayers.